2005
DOI: 10.5713/ajas.2005.165
|View full text |Cite
|
Sign up to set email alerts
|

Association of Candidate Genes with Production Traits in Korean Dairy Proven and Young Bulls

Abstract: This study was performed to offer effective basic data for selection and improvement of Korean dairy cattle through identifying distributional properties among candidate genes (bovine butyrophilin, signal transducers and activators of transcription 5a, and prolactin hormone). In this study, polymorphisms of candidate genes were identified and the relationships between loci and production traits of each gene were analyzed using frozen semen of Holstein bulls (19 proven and 77 candidates). In butyrophilin (BTN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
3
1
1
Order By: Relevance
“…Husani et al (1999) reported similar frequency level for allele A (0.850) and B (0.150). The trend of genotypic profile obtained in the present study also corroborates with the earlier study for Korean bulls, where very high prevalence of AA has been reported (Lee et al 2002, Jang et al 2005.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Husani et al (1999) reported similar frequency level for allele A (0.850) and B (0.150). The trend of genotypic profile obtained in the present study also corroborates with the earlier study for Korean bulls, where very high prevalence of AA has been reported (Lee et al 2002, Jang et al 2005.…”
Section: Resultssupporting
confidence: 92%
“…The frequencies for A and B allele was reported to be 0.891 and 0.109, respectively as against 0.52 and 0.48 observed in the present study. The findings of Jang et al (2005) corroborated with the earlier findings of Chung et al (1998) wherein they have also reported the similar frequencies with respect to AA (0.621) and AB (0.218) genotypes as well as A (0.730) and B allele (0.270). Surprisingly, none of the animals from these studies (Jang et al 2005, Chung et al 1998) exhibited homozygous BB genotype.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Contrary to the present observations (PRL A frequency 0.52), several studies have reported a higher frequency of the PRL A allele in European Holstein (0.95, Chrenek et al 1998), Korean Holstein (0.73, Chung et al 19960.89, Jang et al 2005), Russian Ayrshire (0.86, Udina et al 2001), andGorbatev Red (0.91, Udina et al 2001) cattle. Studies on Korean Holstein (Chung et al 1996;Jang et al 2005) and two Russian cattle (Udina et al 2001) showed a complete absence of the homozygous BB genotype in these breeds. Dybus et al (2005) also presented a higher frequency of AA genotypes in two herds of Black (0.722) and White Polish (0.698) cattle.…”
Section: Resultsmentioning
confidence: 95%